Synthesis, structure and characterizations of a new zinc(II) coordination polymer constructed from 3-(1H-pyrazol-4-yl)-5-(pyridin-2-yl)-1, 2, 4-triazole and isophthalic acid. Issue 6 (3rd June 2018) - Wang, Yu-Fang; Wei, Jing-Jing; Wang, Li-Ya
Abstract: A new Zinc(II) coordination polymer, {[Zn(ip)(H2 L)]·4H2 O}n [H2 ip = isophthalic acid; H2 L = 3-(1H-pyrazol-4-yl)-5-(pyridin-2-yl)-1, 2, 4-triazole], is reported here. It has been structurally characterized by X-ray single crystal analysis, IR spectra, fluorescence spectroscopy, thermogravimetry analysis and X-ray powder diffraction patterns. It belongs to the triclinic system, space group P-1 with a = 8.7934(3) Å, b = 10.1639(3) Å, c = 12.3203(5) Å, α = 75.174(3)°, β = 81.739(3)°, γ = 79.578(4)°, V = 1041.40(7) Å 3, Z = 2, Dc = 1.638 g/cm 3, Mr = 513.77, F(000) = 528, R = 0.0344 and wR = 0.0798. The single X-ray diffraction studies reveal that the compound exhibits 2D layer structure. Moreover, thermal behavior and luminescence properties of the compound were also studied.